Population genomics confirms acquisition of drug-resistant Aspergillus fumigatus infection by humans from the environment - Rhodes, Johanna (2022)
Infections caused by the fungal pathogen Aspergillus fumigatus are increasingly resistant to first-line azole antifungal drugs. However, despite its clinical importance, little is known about how susceptible patients acquire infection from drug-resistant genotypes in the environment. Here, we present a population genomic analysis of 218 A. fumigatus isolates from across the UK and Ireland (comprising 153 clinical isolates from 143 patients and 65 environmental isolates). First, phylogenomic analysis shows strong genetic structuring into two clades (A and B) with little interclade recombination and the majority of environmental azole resistance found within clade A. Second, we show occurrences where azole-resistant isolates of near-identical genotypes were obtained from both environmental and clinical sources, indicating with high confidence the infection of patients with resistant isolates transmitted from the environment. Third, genome-wide scans identified selective sweeps across multiple regions indicating a polygenic basis to the trait in some genetic backgrounds. These signatures of positive selection are seen for loci containing the canonical genes encoding fungicide resistance in the ergosterol biosynthetic pathway, while other regions under selection have no defined function. Lastly, pan-genome analysis identified genes linked to azole resistance and previously unknown resistance mechanisms. Understanding the environmental drivers and genetic basis of evolving fungal drug resistance needs urgent attention, especially in light of increasing numbers of patients with severe viral respiratory tract infections who are susceptible to opportunistic fungal superinfections.